Tongue Untied, Tongue with Tongue. Mining the Binary Matrix - Kancler, Tjaša (Identities: Journal for Politics, Gender and Culture, 2013)
Although language allows boundless freedom, we are at the same time confined within a linguistic structure that first demands that we are assigned a sex and a gender and consequently restricts us to two existing categories; that is, to the categories of male or female. Gender in language therefore forces every individual to mark in its speech to which gender category it belongs. If we are neither women nor men, then how can we understand our existence through language? What is the relation between the binary system of gender (man/woman) and language? How is the relationship between body, language, subjectivity and politics articulated nowadays? In addition, how can we be constituted as political subjects in spite of our non-defining identity? This article considers the questions of deconstruction of the binary man/woman system in relation to the further, possible and common struggle against global capitalism, coloniality and heteropatriarchy. Author(s): Tjaša Kancler Title (English): Tongue Untied, Tongue with Tongue. Mining the Binary Matrix Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 14-19 Page Count: 6 Citation (English): Tjaša Kancler, “Tongue Untied, Tongue with Tongue. Mining the Binary Matrix,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 14-19.